2017
DOI: 10.1080/19396368.2017.1332114
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of laparoscopic surgery of peritoneal endometriosis and endometrioma on the outcome of ICSI cycles

Abstract: Our objective was to assess the role of laparoscopic removal of ovarian endometriomas and ablation of peritoneal endometriosis on the outcome of intracytoplasmic sperm injection (ICSI) - Embryo Transfer cycles by comparing with the results of patients with untreated endometriomas and tubal factor without underlying endometriosis confirmed by laparoscopy. For this purpose, between 2002 and 2015, outcomes of 257 ICSI cycles of 150 patients, including 91 cycles of 48 patients in minimal endometriosis, 57 cycles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Some large-scale studies showed a prevalence of endometriosis in 25% to 40% of infertile women, 5,6 as well as low basal ovarian reserve, low fertility rate, and embryo cleavage. 7 In addition, the pro-inflammatory and angiogenic factors in the ectopic endometrium may contribute to abnormal placentation 2,8 and to develop major obstetrical complications including activation of the mechanisms involved in preterm birth (PB) 1,2,9 ; newborns of these women need more frequent neonatal intensive care unit admissions. 10 However, other studies reported that complications of endometriosis are rare and have no major negative effect on pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some large-scale studies showed a prevalence of endometriosis in 25% to 40% of infertile women, 5,6 as well as low basal ovarian reserve, low fertility rate, and embryo cleavage. 7 In addition, the pro-inflammatory and angiogenic factors in the ectopic endometrium may contribute to abnormal placentation 2,8 and to develop major obstetrical complications including activation of the mechanisms involved in preterm birth (PB) 1,2,9 ; newborns of these women need more frequent neonatal intensive care unit admissions. 10 However, other studies reported that complications of endometriosis are rare and have no major negative effect on pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Guler et al reported that cycle cancellation was significantly higher and clinical pregnancy per cycle and per embryo transfer was significantly lower in the operated endometrioma group in comparison to patients with intact endometriomas, and they concluded that laparoscopic endometrioma cystectomy may worsen IVF/ ICSI outcomes by decreasing ovarian reserve and the quality of oocytes and embryos [20].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased ovarian reserve, is great clinical challenge in reproductive medicine everyday practice of assisted reproduction. Cases suffering from reduced ovarian reserve however different etiologies could have various impact and influences on the IVF/ ICSI clinical outcomes [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…A prior research team of investigators have compared in analytical manner the IVF live birth rates in cases having diminished ovarian reserve issues after performance of ovarian cystectomy for endometrioma with cases having idiopathic issues of diminished ovarian reserve revealing a statistically significantly higher rate of fertilization rate and mean number of embryos but a reduced rates of clinical pregnancy in cases that had an endometrioma excision operative procedure [10,12,13].…”
Section: Discussionmentioning
confidence: 99%